Incidence and Outcomes of Acute Kidney Injury in Patients Admitted to Hospital With COVID-19: A Retrospective Cohort Study. (July 2021) - Pitre, Tyler; Dong, Angela (Hong Tian); Jones, Aaron; Kapralik, Jessica; Cui, Sonya; Mah, Jasmine; Helmeczi, Wryan; Su, Johnny; Patel, Vivek; Zia, Zaka; Mallender, Michael; Tang, Xinxin; et al.
Background: The incidence of acute kidney injury (AKI) in patients with COVID-19 and its association with mortality and disease severity is understudied in the Canadian population. Objective: To determine the incidence of AKI in a cohort of patients with COVID-19 admitted to medicine and intensive care unit (ICU) wards, its association with in-hospital mortality, and disease severity. Our aim was to stratify these outcomes by out-of-hospital AKI and in-hospital AKI. Design: Retrospective cohort study from a registry of patients with COVID-19. Setting: Three community and 3 academic hospitals. Patients: A total of 815 patients admitted to hospital with COVID-19 between March 4, 2020, and April 23, 2021. Measurements: Stage of AKI, ICU admission, mechanical ventilation, and in-hospital mortality. Methods: We classified AKI by comparing highest to lowest recorded serum creatinine in hospital and staged AKI based on the Kidney Disease: Improving Global Outcomes (KDIGO) system. We calculated the unadjusted and adjusted odds ratio for the stage of AKI and the outcomes of ICU admission, mechanical ventilation, and in-hospital mortality. Results: Of the 815 patients registered, 439 (53.9%) developed AKI, 253 (57.6%) presented with AKI, and 186 (42.4%) developed AKI in-hospital. The odds of ICU admission, mechanical ventilation, and death increased as the AKI stage worsened. Stage 3 AKI that occurred during hospitalization increased the odds of death (odds ratio [OR] = 7.87 [4.35, 14.23]). Stage 3 AKI that occurred prior to hospitalization carried an increased odds of death (OR = 5.28 [2.60, 10.73]). Limitations: Observational study with small sample size limits precision of estimates. Lack of nonhospitalized patients with COVID-19 and hospitalized patients without COVID-19 as controls limits causal inferences. Conclusions: Acute kidney injury, whether it occurs prior to or after hospitalization, is associated with a high risk of poor outcomes in patients with COVID-19. Routine assessment of kidney function in patients with COVID-19 may improve risk stratification. Trial registration: The study was not registered on a publicly accessible registry because it did not involve any health care intervention on human participants.